Power system quality assessment. - Arrillaga, Jos, ....-; Chen, S., ....-; Watson, Neville R., ....- (Chichester : Wiley, 2000)
Power Quality Indices and Standards. Power Assessment Under Waveform Distortion. Waveform Processing Techniques. Power Quality Monitoring. Evaluation of Power System Harmonic Distortion. Power Quality State Estimation. Appendices. Index.
Keywords: Elektriciteitsnetten; Elektriciteitsvoorziening; Stabiliteit